2017
DOI: 10.1111/iej.12762
|View full text |Cite
|
Sign up to set email alerts
|

Expression of factors involved in dental pulp physiopathological processes by nemotic human pulpal fibroblasts

Abstract: Le Clerc J, Tricot-Doleux S, Pellen-Mussi P, P erard M, Jeanne S, P erez F. Expression of factors involved in dental pulp physiopathological processes by nemotic human pulpal fibroblasts. International Endodontic Journal, 51, e94-e106, 2018.Aim To investigate in human dental pulp fibroblasts (HDPF) the expression of factors involved in dental pulp physiopathological processes and in an experimental model of cell activation called nemosis, and to compare the behaviour of pulp cell activation with sound lung fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 82 publications
(178 reference statements)
1
9
0
Order By: Relevance
“…Inflammatory reactions are a prerequisite for the migration of progenitor cells involved in pulp repair 3 . An in vitro model of inflammation induced by nemosis verified this 156,157 . In nemosis, normal fibroblasts are induced to form groups, called spheroids, which do not grow but undergo cellular activation and simultaneous programmed cell death 158,159 ; it occurs in DPFs in vitro and could occur in vivo during pulp inflammation 156,160 .…”
Section: Stem Cell Recruitment and Differentiationsupporting
confidence: 62%
See 1 more Smart Citation
“…Inflammatory reactions are a prerequisite for the migration of progenitor cells involved in pulp repair 3 . An in vitro model of inflammation induced by nemosis verified this 156,157 . In nemosis, normal fibroblasts are induced to form groups, called spheroids, which do not grow but undergo cellular activation and simultaneous programmed cell death 158,159 ; it occurs in DPFs in vitro and could occur in vivo during pulp inflammation 156,160 .…”
Section: Stem Cell Recruitment and Differentiationsupporting
confidence: 62%
“…In nemosis, normal fibroblasts are induced to form groups, called spheroids, which do not grow but undergo cellular activation and simultaneous programmed cell death 158,159 ; it occurs in DPFs in vitro and could occur in vivo during pulp inflammation 156,160 . Nemotic fibroblasts release significant amounts of proinflammatory cytokines, chemokines 156 , cyclooxygenase 2 156,157 , VEGF 156 , and hepatocyte growth factor 160 , triggered through direct cell-to-cell adhesion rather than external stimuli 158,160 . Thus, under experimental conditions, nemotic DPFs could be a source of chemokines and cytokines that induce stem cell migration 160 and proangiogenic factors that induce angiogenic responses from endothelial cells during tissue repair 161 .…”
Section: Stem Cell Recruitment and Differentiationmentioning
confidence: 99%
“…Dental caries is a chronic infectious disease, resulting in enamel and dentine demineralization and subsequent pulp tissue injury (Bowen 2016). As the lesion progresses, caries-related microorganisms penetrate dentinal tubules and induce pulpal tissue inflammation, leading to apoptosis of odontoblasts (Le Clerc et al 2018). During inflammation, the pulp tissue releases a series of chemokines and cytokines through congenital or/and acquired immune responses whist responding to bacterial irritants (Jiang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that dental pulp fibroblasts can secret many types of cytokines in response to various stimuli in a similar manner to immune and endothelial cells as well as odontoblasts (3). Cytokines are proteins secreted by innate and adaptive immune cells that act stimulating these cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cytokines of the CXC subfamily, such as IL-8, growth-related oncogene (GRO) and cell-derived stroma (SDF), are potent chemotactic and neutrophil activators (3). Some studies have shown that dental pulp fibroblasts are real sources of chemokines (1,(3)(4)(5). CXCL8, also called IL-8 is produced by a range of cell types, including neutrophils, monocytes, macrophages, fibroblasts, and keratinocytes.…”
Section: Introductionmentioning
confidence: 99%